Statistical evaluation of the corrosive wear of fuel injector elements used in common rail systems - Abramek, Karol Franciszek (Strojniški vestnik, 2015)
This paper presents the causes and consequences of corrosion that has a destructive impact on the technical condition and operational reliability of Common Rail fuel injectors. The analysis included selected components indicating the elements and assemblies most frequently subject to destructive processes. Statistical evaluation of the corrosive wear of fuel injector elements was carried out based on experimental data obtained when verifying the fuel injector designs of different generations using the concept of corrosion density, related to our own classification of the degree of wear. The repair efficiency percentages were specified, taking into account specific operational mileages. Typical problems with the fuel injectors of leading manufacturers, with examples, are also shown.
Keywords: korozija komponent; statistične analize; šobe za vbrizgavanje goriva